CHRONOLOGICAL AGE AND EVENT DIFFERENCES IN ANAEROBIC PERFORMANCE OF YOUNG TRACK AND FIELD ATHLETES - ALPAY GÜVENÇ; TAHİR HAZIR; ÜMİD KARLI; ALPER ASLAN; CANER AÇIKADA (ümit doğan üstün, 2018)
The aim of the present investigation was to evaluate anaerobic performance parameters in young competitive male and female athletes engaged in different events of Track and Field, and to compare them in relation to chronological age for each gender group. Fifty-six 12-to14-year-old girls and sixty-three 11-to16-year-old boys totally 119 athletes were participated in this study. Two event-specific-groups and three chronological-age-groups were constructed for each gender. Event-specific groups were composed of Group 1 (middle-long distance runners) and Group 2 (sprinters, throwers, jumpers). Age groups were consisted of 12, 13 and 14 years old girls, and 11-12, 13-14 and 15-16 years old boys. Body mass and stature were measured. Percentage of body fat and fat free mass were calculated from the appropriate equations. Anaerobic performance was assessed with the Wingate Anaerobic Test. Two-way Analysis of Variance (2×3) was used for statistical analysis. Both absolute and relative anaerobic performance and fatigue index values for each gender were significantly higher in the Group 2 than in the Group 1 (p<0.05). Absolute anaerobic power and capacity values of male athletes significantly increased with age (p<0.01), but when there were normalised with body mass or fat free mass, relative values did not significantly change with age (p>0.05). However, the effects of age on absolute and relative values of anaerobic performance were not significant in female athletes (p>0.05). In conclusion, the level of anaerobic performance was altered depending on event specialization in young Track and Field athletes. This difference may demonstrate the effect of training specificity.